The lipoprotein Pal stabilises the bacterial outer membrane during constriction by a mobilisation-and-capture mechanism - Joanna Szczepaniak (Nature Portfolio, 2020)
The lipoprotein Pal participates in the coordination of outer-membrane constriction with septation in Gram-negative bacteria. Here, the authors show that this coordination is mediated by active mobilisation-and-capture of Pal at division septa by the Tol system.